Knowledge, Attitudes, and Behaviors of Faculty of Medical Students on Energy Drinks - Kuş, Celal; Keten, Hamit Sırrı; Güvenç, Numan; Gümüştakım, Raziye Şule (Addicta: The Turkish Journal on Addictions, 2022)
This study aimed to determine the knowledge, attitudes, and behaviors of medical faculty students regard- ing energy drinks, which are consumed frequently and have various health consequences. The study was conducted with 397 students between May 1 and May 31, 2021. A questionnaire consisting of four parts prepared by the researchers was administered to the students online using Google Forms. The questionnaire was designed to reveal students’ sociodemographic characteristics, smoking and alcohol use, and knowledge, attitudes, and behaviors regarding energy drinks. Data analysis was performed with the Statistical Package for the Social Sciences 20.0 package program, and values of p < .05 were considered statistically significant. The average age of participants was 21.22 ± 3.12 years, and it was found that 234 (58.9%) of the students had consumed energy drinks, while 163 (41.1%) had not. Eighty-three (35.5%) of the students consuming energy drinks and 47 (28.8%) of those not consuming energy drinks stated that they knew the contents of such beverages (p = .104). Our study thus revealed that a significant percentage of students had experience with energy drinks. There is an opinion among students that the consumption of energy drinks increases sports performance. At the same time, it was seen that the students had a serious lack of knowledge about energy drinks.